Research progress of Toll-like receptors in calcified aortic valve disease - REN Yiming; ZHANG Jinhui; WANG Congcong; WANG Tiankun; REN Xuequn; ZHOU Jianliang (Yixue xinzhi zazhi)
Calcified aortic valve disease (CAVD) was believed to be caused by aging-associated degenerative changes and passive calcium deposition. In recent years, it has been found that CAVD is an active pathological process, but the possible pathogenesis of CAVD has not been elucidated. During the development of CAVD, both innate and adaptive immune responses are activated, and increasing evidence suggests that inflammation plays a central role in the initiation and progression of the disease, in which the function of Toll-like receptors (TLRs) is particularly important. TLRs play a crucial role in controlling infection and maintaining tissue homeostasis by identifying host derived molecules released after pathogen and tissue damage, acting as a sentinel for the innate immune system. This article provides an overview of the current concepts regarding the relationship between TLRs signaling and inflammation and calcification remodeling in the pathogenesis of CAVD. The above regulatory mechanisms can provide new targets and strategies for the treatment of CAVD.